Additive Fabrication of Anepectic Meshes controlled by a NiTi alloy - Marcelino, Inês Margarida Neves (2020)
An anepectic material is a metamaterial which simultaneously exhibits a negative coefficient of thermal expansion (CTE) and a negative Poisson coefficient. These meshes may be applied in situations where a response to a thermal stimulus is desired, such as in the aerospace and medical fields. In the current work, anepectic composite meshes, made from ABS and NiTi alloys, were fabricated with the aid of an additive manufacturing technique and subsequently characterized. Seven different mesh designs or material combinations were tested. In every case, a common passive part consists of ABS. A complementary active part, consisting of NiTi wire, differed from case to case, whether in terms of the particular behavior demonstrated (shape memory effect [SME] an/or superelasticity [SE]), the temperature of the relevant phase transformation, the geometry adopted, or the diameter used. All meshes were tested in a silicone bath, and their CTE was measured. The results showed that, under careful parameter selection it is possible to achieve an anepectic effect by combining ABS with SME or SE wires. The mesh that showed to have a more negative CTE (-3008 x 10-6 ºC-1) combined SME wires with SE wires. With such combination, it was possible to activate the mesh bellow the glass transition of the polymer, at 38ºC. For one of the seven fabricated meshes, cyclic tests of three heating and cooling were performed. But only during the first cycle could the anepectic behavior be preserved, the CTE becoming positive on the remaining cycles. Finite element simulation was also performed, where both positive and negative mesh displacements were verified.